Pengembangan Multimedia Pembelajaran PPKn Berbasis Wordwall Untuk Siswa Kelas 6 Sekolah Dasar - Dina Kurniastuti; Sutrisna Wibawa (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Learning media is an important learning tool to consider in the learning process. The presence of learning media can make learning more interesting and active, so that the use of media can help increase student achievement and learning motivation. The presence of learning media in citizenship learning content is considered very important to reduce the verbality of citizenship learning material. The aim of this research is to develop wordwall-based citizenship learninglearning media that can be used by teachers to transfer material and carry out learning evaluations. The type of research used in this research is development research (Research and Development). Research and development is research that aims to produce a product that comes from research and testing the product that has been developed. The development research model is the ADDIE model which consists of five stages of development research. The five stages are analysis, design, development, implementation and evaluation. In this research, the development stage will be discussed up to the ADD stage. The subjects in this research were media experts, material experts, and three 6th grade elementary school students to test the level of appropriateness of the media. Based on the validation test, it can be seen that through the two stages of validation by experts, the wordwall media was declared very suitable for use in learning. This is because wordwall media can have a positive influence on the classroom climate and student learning outcomes.